2019
DOI: 10.1242/dev.177709
|View full text |Cite
|
Sign up to set email alerts
|

Positional information and tissue scaling during development and regeneration

Abstract: In order to contribute to the appropriate tissues during development, cells need to know their position within the embryo. This positional information is conveyed by gradients of signaling molecules, termed morphogens, that are produced in specific regions of the embryo and induce concentration-dependent responses in target tissues. Positional information is remarkably robust, and embryos often develop with the correct proportions even if large parts of the embryo are removed. In this Review, we discuss classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 157 publications
0
27
0
Order By: Relevance
“…Scaling between body size and metabolic or biomechanical properties has been the subject of intense study for decades (29,30). More recently, investigations of the scaling of morphogen gradients with tissue area or length have unveiled novel mechanisms of cell fate specification during development (31,32). Here, we have uncovered a scaling between the number of aSFs per cell and cell apical area in an epithelial tissue.…”
Section: Discussionmentioning
confidence: 79%
“…Scaling between body size and metabolic or biomechanical properties has been the subject of intense study for decades (29,30). More recently, investigations of the scaling of morphogen gradients with tissue area or length have unveiled novel mechanisms of cell fate specification during development (31,32). Here, we have uncovered a scaling between the number of aSFs per cell and cell apical area in an epithelial tissue.…”
Section: Discussionmentioning
confidence: 79%
“…For appropriate tissue formation during development, cells must know their position relative to other cells. In animals, it is well documented that gradients of signaling molecules (morphogens) that convey positional information determine cell fate [37]. Positional information is remarkably missing from plant tissue culture studies as explants are always placed on agar plates or liquid floats or in liquid media.…”
Section: Discussionmentioning
confidence: 99%
“…While no stem cell movement is present in plants, we show that auxin flow direction is a determinant in shoot regeneration. Thus, cells' capability to establish their environment and position is essential to the regeneration process through taxa [37]. It was shown that with the positional change of the root cells' fate, the chromatin state is remodeled [41].…”
Section: Discussionmentioning
confidence: 99%
“…
Despite variability in embryo size, the tissue, organ and body plan develop in proportion with embryo size, known as the scaling phenomenon [1][2][3][4][5][6][7] . Scale-invariant patterning of gene expression is a common feature in development and regeneration, and can be generated by mechanisms such as scaling morphogen gradients 8,9 and dynamic oscillation 10,11 .
…”
mentioning
confidence: 99%
“…The decoder in the cell (usually gene networks) reads the local value of the signal to infer its spatial position by expressing the appropriate genes, as exemplified in the French-flag model 2, 19,20 . A common feature in these processes is that the gene expression pattern generated by the decoder is often scale-invariant with respect to fluctuations in the overall length of the system, which ensures the organism develops in the correct proportion 6,7,[21][22][23][24] . A scale invariant output can be achieved with a scale invariant input.…”
mentioning
confidence: 99%